Linear mixed modeling on the effects of varus knee surgery on the ankle joint weight-bearing axis - Kwon, Soon Sun; Yoo, Jae Doo; Lee, Seung Yeol (Foot and Ankle Surgery, 2022)
Background: Varus knee correction may affect the ankle and subtalar joints and impact the prognosis of ankle arthritis because the weight-bearing load on the lower extremity extends from the hip to the foot. We aimed to evaluate the changes in the mechanical axis and the weight-bearing axis of the ankle after varus knee surgery. Methods: Patients with a varus knee were followed up after undergoing high tibial osteotomy or total knee replacement arthroplasty. The inclusion criteria were age (>18 years) and a history of preoperative and postoperative scanograms. The postoperative change to the ankle joint axis point on the mechanical axis and weight-bearing axis according to the hip–knee–ankle angle correction was adjusted by multiple factors using a linear mixed model. Results: Overall, 257 limbs from 198 patients were evaluated. The linear mixed model showed that the change in the ankle joint axis point on the mechanical axis was not statistically significant after high tibial osteotomy and total knee replacement arthroplasty (p = 0.223). The ankle joint axis point on the weight-bearing axis moved laterally by 0.9% per degree of postoperative hip–knee–ankle angle decrease (p < 0.001). Conclusions: Varus knee correction could affect the subtalar joint and the ankle joint. Our findings require consideration when utilized during pre- and postoperative evaluations using the weight-bearing axis of patients undergoing varus knee correction.
Keywords: Adolescent; Ankle Joint; Arthroplasty, Replacement, Knee; Humans; Knee Joint; Osteoarthritis, Knee; Retrospective Studies; Tibia; Weight-Bearing; High tibial osteotomy; Mechanical axis; Total knee arthroplasty; Varus knee; Weight-bearing axis